Multi Objective Optimization in The Basic of Ratio (Moora) In Supporting Decision Making in Measuring Employee Performance Level Case Study PT. Padi Saga Utama - Dwi Arista, Ruly (International Journal of Science, Technology & Management, 2023)
Staff Employees are the most important assets or human resources owned by a company. in evaluating the work achievement of a staff, the company's management makes a ranking of work results for each work of its staff PT. Padi Saga Utama. The benefit of this research is to assist decision making to measure the level of staff performance who achieves the highest to lowest targets at PT. Padi Saga Utama. The sources used for this research are data taken from the company PT. Padi Saga Utama. The staff data processed were as many as 20 permanent staff who have been registered at PT Padi Saga Utama. data processing using the Multi Objective Optimization on The Basic of Ratio (Moora) method. The results of testing the Morra method obtained that the highest alternative calculation table score is R3 (0.2144), staff with good performance is R3. Based on the results of research conducted, the application of the Multi Objective Optimization method on the Basic of Ratio (Moora) is quite easy to use as the process of measuring the performance level of lecturers.